Human Rights and Black Brazilian Health - Cruz, Isabel CF da (Online Brazilian Journal of Nursing, 2009)
The purpose of this discussion paper is to explore the relationships between inequity and health in Brazil, particularly to Blacks Brazilians. Health as a human right is the focus to help the comprehension the pathways between inequity, racism and disease.